C-(2-Deoxy-d-arabino-hex-1-enopyranosyl)-oxadiazoles: synthesis of possible isomers and their evaluation as glycogen phosphorylase inhibitors. (14th August 2015) - Bokor, Éva; Szennyes, Eszter; Csupász, Tibor; Tóth, Nóra; Docsa, Tibor; Gergely, Pál; Somsák, László
Abstract: Synthetic methods were elaborated ford -glucals attached to oxadiazoles by a C–C bond. Introduction of the double bond was effected by either DBU induced elimination of PhCOOH from the O -perbenzoylated glucopyranosyl precursors or Zn/ N -methylimidazole mediated reductive elimination from the 1-bromoglucopyranosyl starting compounds. Alternatively, heterocyclizations of 2-deoxy-d - arabino -hex-1-enopyranosyl cyanide were also carried out. Test compounds were obtained by Zemplén debenzoylation, however, none of them showed significant inhibition of rabbit muscle glycogen phosphorylase b . Graphical abstract: Highlights: Synthesis ofd -glucals attached by a C-1–C bond to each isomeric oxadiazole. Formation of 1, 2-double bonds by DBU induced elimination. Formation of 1, 2-double bonds by Zn/ N -methylimidazole mediated reductive elimination. No inhibition of rabbit muscle glycogen phosphorylase b .